2019
DOI: 10.1152/ajpcell.00156.2019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of skeletal muscle contraction on CD146+Lin pericytes

Abstract: Unaccustomed resistance exercise can initiate skeletal muscle remodeling and adaptive mechanisms that can confer protection from damage and enhanced strength with subsequent stimulation. The myofiber may provide the primary origin for adaptation, yet multiple mononuclear cell types within the surrounding connective tissue may also contribute. The purpose of this study was to evaluate the acute response of muscle-resident interstitial cells to contraction initiated by electrical stimulation (e-stim) and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Our baseline data from cells isolated before training revealed that the pericytes contained a number of angiogenic factors, known to be of importance for the regulation of capillary growth in skeletal muscle 24 . The levels of VEGF protein were similar in the pericytes and endothelial cells, whereas the levels of TSP‐1 and VEGFR2 were 6‐ and 10‐fold higher, respectively, in the endothelial cells than in pericytes, indicating that pericytes may have a paracrine pro‐angiogenic function, which supports previous evidence of a role in angiogenesis in skeletal muscle 17 , 18 , 30 , 35 , 36 , 37 Structurally, there is a close proximity between pericytes and endothelial cells with shared basement membrane 16 , 37 which would facilitate a directed release of VEGF from the pericyte to the endothelial cells, although direct evidence for such a mechanism is lacking. Somewhat unexpectedly, the pericytes did not express measurable levels of Tie2.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our baseline data from cells isolated before training revealed that the pericytes contained a number of angiogenic factors, known to be of importance for the regulation of capillary growth in skeletal muscle 24 . The levels of VEGF protein were similar in the pericytes and endothelial cells, whereas the levels of TSP‐1 and VEGFR2 were 6‐ and 10‐fold higher, respectively, in the endothelial cells than in pericytes, indicating that pericytes may have a paracrine pro‐angiogenic function, which supports previous evidence of a role in angiogenesis in skeletal muscle 17 , 18 , 30 , 35 , 36 , 37 Structurally, there is a close proximity between pericytes and endothelial cells with shared basement membrane 16 , 37 which would facilitate a directed release of VEGF from the pericyte to the endothelial cells, although direct evidence for such a mechanism is lacking. Somewhat unexpectedly, the pericytes did not express measurable levels of Tie2.…”
Section: Discussionsupporting
confidence: 84%
“…In general, content of angiogenic proteins have never been determined in isolated skeletal muscle‐derived endothelial cells and pericytes. Pericytes are of interest in this context as evidence is accumulating for their role in skeletal muscle angiogenesis 16‐18 . Moreover, it is feasible that the time course and relative magnitude of change in endothelial cells and pericytes differs from that in whole muscle.…”
Section: Introductionmentioning
confidence: 99%
“…E-stim mice were subjected to bilateral electrical stimulation of the sciatic nerve as previously described 21 . Prior to treatment, mice were anesthetized using isoflurane at a concentration of 2–5% during induction.…”
Section: Methodsmentioning
confidence: 99%
“…Pericytes have been shown to express a range of different markers, individually and in combination (Armulik et al, 2011;Hsu et al, 2019). The most commonly used include Rgs5 (Bondjers et al, 2003), Pdgfrβ (Armulik et al, 2011), Nestin (Birbrair et al, 2013a), Tbx18 , CD146 (Dvoretskiy et al, 2019), and Neural/glial antigen 2 (Ng2) (Armulik et al, 2011). However, none of these markers are pericyte specific as each marker can identify multiple dermal cell populations; for example Pdgfrβ is also expressed by adventitial fibroblasts (Stapor et al, 2014) and CD146 is also expressed by endothelial cells (Crisan et al, 2008;Guerrero-Juarez et al, 2019;Gay et al, 2020;Haensel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%